Налоговое право России: курс лекций / И. И. Кучеров - Кучеров Илья Ильич (Библиотека "ЮрИнфоР", 2006)
Экземпляры: СЭ (20071206) / Инвентарный номер: 1066973 / Цена: / Сис.шифр: 67.402 / Авт.знак: К 95 / ГРНТИ: 10 / ББК: 67.402.23я7